THE EFFECT OF BURNOUT AND WORK STRESS ON EMPLOYEE PERFORMANCE AT PT ARTERIA DAYA MULIA CIREBON - Kurniawansyah Kurniawansyah; Agi Syarif Hidayat (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study aims to analyze the effect of burnout and work stress on the performance of employees at PT Arteria Daya Mulia in Cirebon. The research applies an associative quantitative approach using a survey method involving employees from the production division. Data were collected from selected respondents and analyzed using multiple linear regression with the assistance of SPSS. The results indicate that burnout does not have a significant effect on employee performance. Similarly, work stress also does not show a significant influence on employee performance. When examined simultaneously, burnout and work stress together do not significantly affect the performance of employees at PT Arteria Daya Mulia Cirebon. These findings suggest that other factors outside the variables examined in this study may play a more important role in determining employee performance. Keywords: Burnout; Work Stress; Employee Performance